Sending Jobs Offshore from the United States: What are the Consequences? - Charles J. Whalen (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2005)
First paragraph: In the United States, the Fourth of July is usually a day of celebration. But the date has a darker meaning for families of more than a thousand workers in central New York. That is because Independence Day, 2004, was when Carrier Corporation halted its Syracuse-area production of cooling equipment, and 1,200 hourly and salaried employees watched their jobs move to Asia (Fay 2005). Carrier workers are not alone. In July 2005, U. S. manufacturing employment totaled 14.3 million, down three million since July 2000. That is a loss of about 20 percent of America's manufacturing jobs in just a few years.
Keywords: 330